RobotX challenge 2022: mechanical design of surface vehicle - Du, Jiajun (Nanyang Technological University, 2023)
Unmanned Surface Vehicles (USV), smaller and remotely operated compared to manned vessels, provide practicality, mobility, and affordability for oceanographic and biological research applications. To achieve full autonomy for USV, advanced sensor systems, communication systems, and AI-based machine learning algorithms are essential for data processing and adapting to changing conditions. This report concentrates on developing the WAM-V16 USV, which is manufactured by Marine Advanced Robotics, for the Maritime RobotX Challenge, an international competition promoting autonomous maritime robotic system development. It evaluates capabilities and promotes innovation through real-world scenario tasks. Accessory design and performance optimization are addressed for the USV through meticulous design, robust mechanical engineering simulations, and precise force calculations. The report includes competition rule analysis, design solution evaluations, conceptual designs for Team Singaboat, center of mass calculation, material selection, and static structural analysis. The real-world implementation is carried out to demonstrate the physical results. All parts will be used in the upcoming Maritime RobotX Challenge 2024, with testing planned for the near future.